PEMANFAATAN TEKNOLOGI DALAM PENGOLAHAN DAN DISEMINASI DATA STATISTIK DI BPS DELI SERDANG - Fauziah Azzahra; Nurjanah, Ella Budi Lestari, Ika Regitami Siregar, Fibri Rakhmawati (JOURNAL OF COMMUNITY DEDICATION, 2025)
In today's digital era, information technology plays a key role in supporting the efficiency and effectiveness of statistical data processing and dissemination. With the development of information technology, the data collection process becomes more automated and integrated. This research aims to analyse how BPS Deli Serdang utilises technology in the processing and dissemination of statistical data. This research uses a qualitative descriptive approach, which aims to describe in depth the use of technology in the process of processing and disseminating statistical data at BPS Deli Serdang. The results of this study obtained that the use of technology at BPS Deli Serdang has increased efficiency and accuracy in the processing and dissemination of statistical data, and the use of  Statistical Information Systems accelerates the processing process, while digital platforms such as BPS Online facilitate data access by the public.